Language Functions in English Language Teaching Materials: A Case Study of Indonesian Secondary School Textbooks of English - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
One of the materials discussed in local English textbooks for secondary school students is language functions. They cover speech acts such as making invitations, requests, or giving opinions. These speech acts should be performed based on meta-pragmatic information—that is when, where, and to whom it is appropriate to perform a particular speech act and what expression would or would not be appropriate in a particular context of culture and context of situation. This study aimed at examining the types and the frequencies of speech acts based on Searle’s speech acts taxonomy and investigating whether or not the language functions are realized based on meta-pragmatic information. One of the findings of this research was most of the language functions discussed in the textbooks are directives and expressives. Another finding was they lacked of meta-pragmatic information. For example, there was no explicit information about the relationship between the speakers, for instance, how close they feel to one another. Keywords: language functions, meta-pragmatic information